Constructive dismissal: The management dynamics - Md Desa, Md Rejab (2014)
Constructive dismissal a fiction of law wherein a worker ceases employment simpliciter at his own violation consequential upon the infringement of the employer who transgressed on his contractual obligation hence breaching the contract of employment.The worker resigned immediately and henceforth commenced legal redress through filing a suit for constructive dismissal.The abundance of such cases reflect the gravity of the transgression and as it strikes to the core issue of one’s livelihood which has been liken to one proprietary right guaranteed under the Federal constitution which are the mirror reflection in this respect of the Universal Declaration of Human Rights 1948.The law as it stands approved this notion of legal fiction as developed by the common law which underlying principles have been firmly established in our jurisprudential reasoning in many cases rehearsed before our courts. The liberties to file an action by the workers are all constitutional guarantee.The functional role by the judiciary is to decide on laws and facts and to redress the grievances in a just and equitable manner within the confined of their findings. However, “constructive dismissal” is an internal issue within an organization and its solution too could be internally devised.The humanistic approach seems plausible to mitigate the rising tide through admittedly as all of us are litigation free since no one could stop us from excising that right which is constitutionally guarantee.Friction in industrial relation do occur since there are divergence of interest within the industry stakeholders as well as the rebellious impulse innate in us as well as other variables that fuelled up the inertia for one to disagree and resent.The very least the figure could be suppressed through dauntingly impossible to eliminate as reasoned above said.